2018
DOI: 10.1038/s41388-018-0264-6
|View full text |Cite
|
Sign up to set email alerts
|

Pre-neoplastic pancreas cells enter a partially mesenchymal state following transient TGF-β exposure

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is a deadly disease and a major health problem in the United States. While the cytokine TGF-β has been implicated in PDAC development, it can exert both pro- and anti-tumorigenic effects that are highly context dependent and incompletely understood. Using three-dimensional (3D) cultures of KrasG12D-expressing mouse pancreatic epithelial cells we demonstrated that while exposure to exogenous TGF-β induced growth arrest of the KrasG12D cells, its subsequent removal allowed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…Moreover, when detected they appear to be associated with neutrophils, and predict shorter progression-free survival due to their higher metastatic potential [152]. In line with these works, hysteresis, or bistability of cellular states, drives TGF-beta—Zeb1 induced EMT in most normal and tumor mammary epithelial cells, as reflected by the bimodal distribution of high and low E-cadherin expression levels of cells exposed to TGF-beta, even after transient exposure, resulting in a more efficient tumor initiation and metastasis induction [153,154].…”
Section: Emt Ctcs and Metastasismentioning
confidence: 88%
“…Moreover, when detected they appear to be associated with neutrophils, and predict shorter progression-free survival due to their higher metastatic potential [152]. In line with these works, hysteresis, or bistability of cellular states, drives TGF-beta—Zeb1 induced EMT in most normal and tumor mammary epithelial cells, as reflected by the bimodal distribution of high and low E-cadherin expression levels of cells exposed to TGF-beta, even after transient exposure, resulting in a more efficient tumor initiation and metastasis induction [153,154].…”
Section: Emt Ctcs and Metastasismentioning
confidence: 88%
“…Induction of EMT has been shown to arrest the cell cycle (Lovisa et al, 2015;Vega et al, 2004). Another study has shown that cells that have undergone a partial EMT can exhibit a hyper-proliferative phenotype (Handler et al, 2018). Here, we considered a simpler case wherein both division and death rates are independent of the phenotype of the cell.…”
Section: Developing a Population-level Model Of Emp Dynamicsmentioning
confidence: 99%
“…However, the ability of aTGFβ1 to interfere with the growth-arresting and, hence, tumor-suppressive function of (exogenous) TGFβ1 also makes it a potential oncogenic driver in early PDAC and BC development. Interestingly, murine pre-neoplastic pancreatic epithelial cells with mutant KRAS transiently exposed to exogenous TGFβ1, i.e., corresponding in vivo to pulses of TGFβ1 produced during chronic pancreatitis, a known risk factor for PDAC [ 54 ], converted to a partially mesenchymal (PM), progenitor-like, and hyper-proliferative state in vitro, which was stable and maintained by aTGFβ [ 27 ]. These PM cells, like Panc1, shared molecular and phenotypic features with the quasi-mesenchymal subtype of human PDAC and in vivo formed ductal structures resembling human PanINs.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, constitutively repressing endogenous TGFβ1 expression and aTGFβ activity in human colon carcinoma cells retained their functional receptor complexes and the ability to respond to exogenous TGFβ but led to a more progressed phenotype [ 19 ]. In order to abrogate aTGFβ signaling, the majority of studies have used either dominant-negative inhibition [ 20 , 21 , 22 , 23 ], reconstitution of the type II receptor (TβRII) [ 18 , 24 ], or inhibition of the activin receptor-like kinase 5 (ALK5) kinase activity [ 20 , 25 , 26 , 27 ] (for a comprehensive review see [ 28 ]). However, these approaches have important limitations for the following reasons: (i) they did not allow for a discrimination between the effects of the three different TGFβ isoforms, TGFβ1, 2, and 3, (ii) aTGFβ1 has been reported to be able to signal with respect to target gene expression, invasion but not proliferation in colon cancer cells that have lost the ability to produce functional TβRII as a result of microsatellite instability [ 25 ], and (iii) they are expected to alter the response to both exogenous and aTGFβ1 and thus preclude an assessment of how exogenous TGFβ1 interacts with aTGFβ1.…”
Section: Introductionmentioning
confidence: 99%